Analisis Kesalahan Afiksasi dalam Karangan Narasi Peserta Didik Kelas V Sekolah Dasar - Addenia Izzah Az-Zahra; St Y Slamet; Roy Ardiansyah (Universitas Sebelas Maret, 2024)
This study aims to describe: (1) errors in the use of affixation, and (2) factors causing the occurrence of affixation errors in the narrative essays of fifth-grade students in Elementary School. This study is a qualitative descriptive study, and the data used are the students' narrative essays and informants (fifth-grade students). The data collection methods include document analysis and interviews. The validity of the data is triangulated using the triangulation technique. The analysis of the data used is Tarigan Language Error Analysis. The results of this study are as follows. First, the results of document analysis of narrative essays of fifth grade students show that the affixation errors found in the students' narrative essays are 146 errors (23.4%) out of 624 affixations found in the students' narrative essays. The affixation errors found in the students' narrative essays consist of 124 prefixation errors (19.87%), 17 suffixation errors (2.73%), and 5 confixation errors (0.8%). Second, the factors causing affixation errors in students' narrative essays include: (1) lack of understanding of affixation rules, (2) lack of understanding in the use of affixes, (3) lack of carefulness and haste when writing narrative essays, and (4) influence of the first language that is more familiar.